In vivo diffusion MRS investigation of non‐water molecules in biological tissues. (21st January 2016) - Cao, Peng; Wu, Ed X.
Abstract : Diffusion MRS of non‐water molecules offers great potential in directly revealing various tissue microstructures and physiology at both cellular and subcellular levels. In brain, 1 H diffusion MRS has been demonstrated as a new tool for probing normal tissue microstructures and their pathological changes. In skeletal muscle, 1 H diffusion MRS could characterize slow and restricted intramyocellular lipid diffusion, providing a sensitive marker for metabolic alterations, while 31 P diffusion MRS can measure ATP and PCr diffusion, which may reflect the capacity of cellular energy transport, complementing the information from frequently used 31 P MRS in muscle. In intervertebral disk, 1 H diffusion MRS can directly monitor extracellular matrix integrity by quantifying the mobility of macromolecules such as proteoglycans and collagens. In tumor tissue, 13 C diffusion MRS could probe intracellular glycolytic metabolism, while 1 H diffusion MRS may separate the spectrally overlapped lactate and lipid resonances. In this review, recent diffusion MRS studies of these biologically relevant non‐water molecules under normal and diseased conditions will be presented. Technical considerations for diffusion MRS experiments will be discussed. With advances in MRI hardware and diffusion methodology, diffusion MRS of non‐water molecules is expected to provide increasingly valuable and biologically specific information on tissue microstructures and physiology, complementing the traditional diffusion MRI of small and ubiquitous water molecules. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this review, recent diffusion MRS studies of biologically relevant non‐water molecules under normal and diseased conditions will be presented. Technique considerations for diffusion MRS experiments will be discussed. With advances in MRI hardware and diffusion methodology, diffusion MRS of non‐water molecules is expected to provide increasingly valuable and biologically specific information on tissue microstructures and physiology, complementing the traditional diffusion MR of small and ubiquitous water molecules.